Khorezm Historical Monuments Are An Important Factor For The Spiritual And Moral Education Of The Young Generation (Zien Journal of Social Sciences and Humanities, 2021)
This article discusses the fact that the monuments of Khiva, one of the international tourist centers, recognized as an open-air museum around the world, are an important factor in the spiritual and moral education of the younger generation.